The trends and hotspots of research on non-pharmacological interventions for labor pain management: a bibliometric analysis - Barut, Suemeyye; Sabanci Baransel, Esra; Celik, Osman Tayyar; Ucar, Tuba (Taylor & Francis Ltd, 2024)
IntroductionThis study aimed to examine important points of focus, trends, and depth of research on non-pharmacological interventions for the management of labor pain worldwide from a macro perspective and present an extensive definition of research fields regarding non-pharmacological interventions.MethodsBibliometric methods were used in this study. With comprehensive keyword lists, the Web of Science and PubMed databases were searched using different screening strategies for publications made until 25 February 2023.ResultsStudies on non-pharmacological interventions in the management of labor pain have continued to develop since 2003 with great momentum. In this study, the most productive country in research on non-pharmacological interventions was found to be Iran, while Australia, the USA, China, and the United Kingdom were the most notable ones in terms of collaboration. The most prevalently studied non-pharmacological interventions were hydrotherapy and acupuncture. The results of the co-word analysis revealed 5 main themes about this field of research.ConclusionThe results of this study showed that interest in studies on non-pharmacological interventions in the management of labor pain has increased, the quality of research in the field is high, international collaboration is increasingly higher, and technological approaches have started to emerge in relevant studies.
Keywords: Bibliometrics; labor pain; non-pharmacological; pain management